(3JNWjW h EfJGL GdehGO GdSeYHUQjI (B/s - (3YHO GdJhGH, TQa GdOjfs; (3cjeHs ((3GdbGgQI (B:s (3GdOGQ GdOhdjI ddESJKeGQGJ GdKbGajI T(B.(3e(B.(3e ,s, 2000)
(3JNWjW h GfJGL GdehGO GdSeYHUQjI fJjLI ddTchc GdcKjQI GdJj CKjQJ Mhd aYGdjI WQb GdJYdje GdJbdjOjI GdJj JQcR Ydi GdeYde abO JhLg GdGgJeGe Gdi GdehGO GdSeYHUQjI h GdJj JYO GcKQ LPHG h aYGdjI aj JhUjd GdLRFjGJ GdUYHI GdJj dG JYdb HGdPgf h eTGQcI GdWGdH aj GfJGL h GSJNOGe GdehGO GdSeYjHUQjI ef CadGe h UhQ h TaGajGJ JLYdg jTYQ HGf dg OhQG aj GdYedjI GdJYdjejI ceG GfgG JhVM GdeYdheGJ h JKHJgGs
Keywords: (3EPGYI h JdaRjhfs; (3GdSeYj GdHUQjs; (3GdEYdGes